2011
DOI: 10.1186/1472-6823-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic disparity in 21-hydroxylase gene mutations identified in Pakistani congenital adrenal hyperplasia patients

Abstract: BackgroundCongenital adrenal hyperplasia (CAH) is a group of autosomal recessive disorders caused by defects in the steroid 21 hydroxylase gene (CYP21A2). We studied the spectrum of mutations in CYP21A2 gene in a multi-ethnic population in Pakistan to explore the genetics of CAH.MethodsA cross sectional study was conducted for the identification of mutations CYP21A2 and their phenotypic associations in CAH using ARMS-PCR assay.ResultsOverall, 29 patients were analyzed for nine different mutations. The group co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Similar genetic homogeneity was detected in the Yupik Eskimos from Western Alaska where high incidence of SWCAH and only homozygosity for the In2G mutation was found 1 . Khan et al found a high variety of mutations in patients with CAH in different Indian ethnicities, except in the Urdu ethnicity, where 8 out of 10 carried In2G mutation of which 5 were homozygous 36,37 . However, connection between the Roma and the Urdu populations remains to be explored.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Similar genetic homogeneity was detected in the Yupik Eskimos from Western Alaska where high incidence of SWCAH and only homozygosity for the In2G mutation was found 1 . Khan et al found a high variety of mutations in patients with CAH in different Indian ethnicities, except in the Urdu ethnicity, where 8 out of 10 carried In2G mutation of which 5 were homozygous 36,37 . However, connection between the Roma and the Urdu populations remains to be explored.…”
Section: Discussionmentioning
confidence: 61%
“…1 Khan et al found a high variety of mutations in patients with CAH in different Indian ethnicities, except in the Urdu ethnicity, where 8 out of 10 carried In2G mutation of which 5 were homozygous. 36,37 However, connection between the Roma and the Urdu populations remains to be explored. Especially.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 13 31 32 ] In SV type, p.I172N mutation was found to be high and this trend was reported in many studies. [ 22 25 33 34 ] I172N is the only one mutation specifically associated with the SV form of the disease, and mutation of this hydrophobic residue to a polar residue results in an enzyme with approximately 1% or normal activity. [ 21 35 ] The frequency of p.P30L mutation was relatively high in our study, when compared with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…One of the PND studies carried out on 24 pregnancies reported I2g mutation in 52 per cent and deletions in 22 per cent of the alleles 26 . Overall, I2g is the single most prevalent mutation reported from other ethnic populations as well as from Indian studies 24 27 28 .…”
Section: Discussionmentioning
confidence: 96%